Reconsidering Identity in Wendt’s “Anarchy Is What States Make of It”: Limits and Extensions - Satria Alamsyah, Mirah (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
This article revisits Alexander Wendt’s constructivist framework on state identity and behaviour in an anarchic international system. Wendt emphasizes that anarchy is a social construct and that identities and interests shape state actions. However, his framework has limitations, particularly in explaining how identities form from the societal to the state level, and in the role of cognition and deliberation at the state level, which are essentially individual capacities. Drawing on Bruce Cronin’s insights, Oran Young’s social choice theory, Maja Zehfuss’ distinction between social and corporate identities, and critiques by Copeland and Boulding on intention interpretation, this article highlights overlooked complexities. The analysis suggests that enriching Wendt’s framework with complementary perspectives allows for a more robust understanding of identity as a key factor shaping intentions, interactions, and the meaning of anarchy, reinforcing constructivism’s relevance in international relations studies.